2019
DOI: 10.3389/fgene.2019.00463
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR Measurement of miR-371a-3p and miR-372-p Is Influenced by Hemolysis

Abstract: Cell-free microRNAs have been reported as biomarkers for several diseases. For testicular germ cell tumors (GCT), circulating microRNAs 371a-3p and 372-3p in serum and plasma have been proposed as biomarkers for diagnostic and disease monitoring purposes. The most widely used method for quantification of specific microRNAs in serum and plasma is reverse transcriptase real-time quantitative PCR (RT-qPCR) by the comparative Ct-method. In this method one or several reference genes or reference microRNAs are neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
0
29
2
Order By: Relevance
“…Hence, it is fair to assume that the same cutoffs determined by the authors are not necessarily applicable in our workflow. Indeed, hemolysis did not show significant direct impact on the microRNA isolation procedure (denoted by ath-miR-159a) nor on the specific target assay miR-372a-3p, which contrasts with the findings of Myklebust and coworkers [43]. An effect on the normalizer miR-30b-5p levels was depicted; however, such effect was minor and seen mainly at the expense of cases with severe hemolysis, with visual scores of 4-5 ( Figure 8), which were absent in our study cohorts.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Hence, it is fair to assume that the same cutoffs determined by the authors are not necessarily applicable in our workflow. Indeed, hemolysis did not show significant direct impact on the microRNA isolation procedure (denoted by ath-miR-159a) nor on the specific target assay miR-372a-3p, which contrasts with the findings of Myklebust and coworkers [43]. An effect on the normalizer miR-30b-5p levels was depicted; however, such effect was minor and seen mainly at the expense of cases with severe hemolysis, with visual scores of 4-5 ( Figure 8), which were absent in our study cohorts.…”
Section: Discussioncontrasting
confidence: 93%
“…The value of this standardized pipeline relies on appropriate quality control and normalization [23,29]. However, some important issues remain, such as hemolysis content in blood samples, as it can interfere with the detection levels of certain microRNAs [42,43], as well as the choice of analysis of serum or plasma. However, the real impact of these matters on specific assays and the best way to approach them is still debatable.…”
Section: Introductionmentioning
confidence: 99%
“…First, the lack of a pre-operative serum samples to confirm the detection of miR-371a-3p in the patient which enables us only to be able to indirectly conclude the high specificity of this biomarker under this condition based on our previous findings [15]. Another limitation is the use of the proper housekeeping gene from serum, as some newer studies also reported issues about pre-analytical influence of haemolysis on the concentration of the serum-based microRNAs [20,21]. In addition, we cannot rule out a lack of expression of this microRNA in the cancer tissue of our patient.…”
Section: Discussionmentioning
confidence: 97%
“…As a further consequence, the determination of miR-371a-3p and miR-372-3p (which themselves are not affected by hemolysis) can be falsified, thus adversely affecting the diagnosis. Therefore, hemolysis and any kind of contamination of the samples should be avoided, or other miRNAs should be considered as endogenous calibrators and normalizers [85].…”
Section: Mir-371a-3pmentioning
confidence: 99%